2018
DOI: 10.1103/physrevb.98.134507
|View full text |Cite
|
Sign up to set email alerts
|

Disorder protected and induced local zero-modes in longer-range Kitaev chains

Abstract: We study the effects of disorder on a Kitaev chain with longer-range hopping and pairing terms which is capable of forming local zero energy excitations and, hence, serves as a minimal model for localization-protected edge qubits. The clean phase diagram hosts regions with 0, 1, and 2 Majorana zero-modes (MZMs) per edge. Using a semi-analytic approach corroborated by numerical calculations of the entanglement degeneracy, we show how phase boundaries evolve under the influence of disorder. While in general the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(71 reference statements)
0
24
0
Order By: Relevance
“…Although we do not do so here, one could also consider quench protocols in which the final Hamiltonian is non-Hermitian, which captures certain gain and/or loss processes. In doing so, one must be careful to consider the relationship between symmetries of the initial state and the non-Hermitian Hamiltonian, the latter of which can have a more general set of symmetries 39 . Note, however, that this work is concerned with properties of the instantaneous wavefunction rather than the spectrum of the Hamiltonian, in contrast to previous studies of non-Hermitian topology [35][36][37][38] .…”
Section: Symmetry Of the Time-evolved Statementioning
confidence: 99%
See 1 more Smart Citation
“…Although we do not do so here, one could also consider quench protocols in which the final Hamiltonian is non-Hermitian, which captures certain gain and/or loss processes. In doing so, one must be careful to consider the relationship between symmetries of the initial state and the non-Hermitian Hamiltonian, the latter of which can have a more general set of symmetries 39 . Note, however, that this work is concerned with properties of the instantaneous wavefunction rather than the spectrum of the Hamiltonian, in contrast to previous studies of non-Hermitian topology [35][36][37][38] .…”
Section: Symmetry Of the Time-evolved Statementioning
confidence: 99%
“…∈ Z 2 . As a toy model of such a system (analogous to the one used to demonstrate mixing in class DIII in 66 ), we use a semi-infinite extended Kitaev chain with beyond-nearest-neighbour hopping and pairing 39,67…”
Section: B Local Adiabatic Mixing Of Edge Modesmentioning
confidence: 99%
“…However, in some instances it has been shown that engineered systemenvironment couplings can actually enhance or even generate quantum correlations, such as entanglement [9][10][11][12][13][14][15][16][17][18]. While robustness of coherence times for edge spins has been extensively studied in the presence of interactions or of integrability-breaking terms and also in the presence of disorder in the Hamiltonian [1,2,19], less is known about their behavior under irreversible open quantum dynamics [20][21][22][23][24]. In particular, it is not clear whether under Markovian (memory-less) dynamics these long edge time-correlations can be observed and general conditions for their existence are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the experimental observation of the topological Anderson insulator has been reported in 1D disordered atomic chain based * binzhou@hubu.edu.cn on the SSH model [64] and optical lattices [65]. In addition, the disorder-induced topological phases in TSCs have also attracted much attention [66][67][68][69]. Analogous to the topological Anderson insulator, Borchmann et al proposed the concept of the Anderson topological superconductor, a disorder-induced topological state in superconductor systems [66].…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to the topological Anderson insulator, Borchmann et al proposed the concept of the Anderson topological superconductor, a disorder-induced topological state in superconductor systems [66]. Recently, Lieu et al studied disorder effects on Kitaev chain model with longer-range hopping and pairing terms, and presented the transformation of phase boundaries under the influence of disorder [68]. Moreover, the combined effects of disorder and interaction in the Kitaev chain model have also been investigated by several research groups [70][71][72][73][74].…”
Section: Introductionmentioning
confidence: 99%